Ethnicity, Culture and Indigenous Leadership in Modern Politics: The Case of the Kadazandusun in Sabah, East Malaysia - Arnold Puyok; Tony Paridi Bagang (Kajian Malaysia, 2011)
This paper is based on an on-going study that examines the role of ethnic identity, cultural unity and indigenous leadership institutions in shaping political change among the Kadazandusuns. The analysis of the three issues is complemented by a survey conducted in 2009 among 200 Kadazandusuns from Kota Kinabalu, Ranau and Tambunan. The preliminary findings suggest that ethnic identity remains a crucial component in the political survival of the Kadazandusuns. The Kadazandusun political elites not only use the identity issue as a 'bargaining tool' but also use this issue to raise ethnic sentiment to win popular support. A majority of the Kadazandusuns surveyed in the study believed that the identity issue has been used for political mileage and that it is time for the Kadazandusun leaders to solve the issue once and for all. All of the Kadazandusun-based cultural associations remain an important 'grassroots base' for the Kadazandusun political elites. The respondents believed that the Kadazandusun political leaders are not united and should be blamed for causing the Kadazandusuns to split. Joseph Pairin Kitingan is seen as the prominent figure that is capable of uniting the Kadazandusuns. Although his status as Huguan Siou is relevant to some Kadazandusuns, other respondents wanted Pairin not to use his Huguan Siou title for political expediency.